Parametric Design on Weld Characteristics of Submerged Arc Welding Process Parameters - Mamunuri, Sailender (International Journal of Engineering and Technology, 2018)
A low carbon with manganese steel is apt for the fabrication of pressure vessels welds, which is designed for low-temperature service requirement. Submerged Arc Welding (SAW) is chosen process, due to incessant sound joint requirement and its inherent qualities like smooth bead, deep penetration and sound joint quality and reliable. SAW is renowned by huge quantity of parameters, which acts collectively influence the outputs performance, subsequently affects the joint quality. The objective is to optimize the variables parametrically for various outputs. Taguchiâ€™s orthogonal array, which is a design of experiment, is adopted to optimize as well for their effects on desired outputs. The author modified the process by introducing â€˜purging gasâ€™ in SAW. â€˜Purgedâ€™ SAW results are contrasted against the traditional â€˜as-isâ€™ of SAW. Identified the variable significance effect is through analysis of variance with their contribution. Correlations between parameters and performance outputs are established via Regression Analysis. Build models competency are checked with F-test; determined quantitatively and showed graphically, for discussion of their effects to achieve the required quality. Using confirmation tests, the models are validated and found the outcomes are in the confines.Â Â